2013
DOI: 10.7773/cm.v39i1.2162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the combined disposal of sewage and brine on meiofauna

Abstract: ABSTRACT.Confluence of anthropogenic influences is common in coastal areas (e.g., disposal of different pollutants like industrial and domestic sewage, brine, etc.). In this study we assessed whether the combined disposal of domestic sewage and brine altered patterns in the abundance and assemblage structure of subtidal meiofauna inhabiting sandy seabeds. ) from the discharge outfall. This pattern was particularly accentuated for nematodes. Proximity to the discharge point also altered patterns in meiofaunal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
1
4
1
4
Order By: Relevance
“…Our results indicate the negative impact of anthropogenic activities on the water quality of the La Michoacana drain. Several reports have shown the environmental damage and health risk associated with the discharge of residual wastewater into water bodies worldwide (e.g., Opisa et al 2011, Bagordo et al 2012, Matano et al 2013, Riera et al 2013. In 1997, 75% of the water and 72% of the mollusk samples obtained from two Sinaloan lagoons (Bahía de Altata and Ensenada El Pabellon) presented TC and FC contents above the Official Mexican Norm (NOM-113-SSA1-1994), making the mollusks unsuitable for consumption (Haws et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results indicate the negative impact of anthropogenic activities on the water quality of the La Michoacana drain. Several reports have shown the environmental damage and health risk associated with the discharge of residual wastewater into water bodies worldwide (e.g., Opisa et al 2011, Bagordo et al 2012, Matano et al 2013, Riera et al 2013. In 1997, 75% of the water and 72% of the mollusk samples obtained from two Sinaloan lagoons (Bahía de Altata and Ensenada El Pabellon) presented TC and FC contents above the Official Mexican Norm (NOM-113-SSA1-1994), making the mollusks unsuitable for consumption (Haws et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros resultados demuestran el impacto negativo de las actividades antropogénicas sobre la calidad del agua del canal de drenaje La Michoacana. Diferentes investigaciones han demostrado el daño ambiental y el riesgo para la salud que causan las descargas de aguas residuales a los cuerpos de agua en varias partes del mundo (e.g., Opisa et al 2011, Bagordo et al 2012, Matano et al 2013, Riera et al 2013. En 1997, el 75% de las muestras de agua y el 72% de las muestras de moluscos obtenidas de la bahía de Altata y Ensenada El Pabellón (Sinaloa) presentaron contenidos de CT y CF por encima de la norma Mexicana (NOM-113-SSA1-1994), lo cual provocó que los moluscos fueran inadecuados para el consumo (Haws et al 2006).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Potential ecological indicators of desalination to marine ecosystem investigation were conducted to describe biological damage to amphipod, bivalve, copepod, infauna, or the number of organisms which can be used for future report [90][91][92][93]. Previous studies have shown that the amphipod species Ampelisca brevicornis survival is a sensitive organism to assess the toxicity of contaminated sediment [94][95][96].…”
Section: Amphipod Bivalve and Copedodmentioning
confidence: 99%